SISTEM PENDUKUNG KEPUTUSAN PEMBERIAN INFRASTRUKTUR PEMBELAJARAN PASCA PANDEMI UNTUK SEKOLAH DI LINGKUP DINAS PENDIDIKAN KABUPATEN MADIUN DENGAN METODE ANALYTICAL HIERARCHY PROCESS (AHP) DAN TECHNIQUE FOR ORDER PREFERENCE BY SIMILARITY TO IDEAL SOL - Eka Bayu Bimantara; Fatim Nugrahanti; Latjuba Sofyana (LPPM Universitas Merdeka Madiun, 2023)
Decision Support System is a system that is used to assist in making decisions on a semi-structured type of problem, such as choosing an appropriate school to given learning infrastructure. The AHP method is a more efficient decision-making method because it presents detailed data by comparing all criteria and alternative. Calculations used to solve problem use multiplication to connect preference values, where the value for each criteria and alternative must be searched for the eigen / priority vector, after which the consistency proven using RI table (ratio index), if result proof is less than 10% (0.1) then it’s declared consistent and calculation can be continued, but if results prove more than 10% (0.1) then calculation is considered inconsistent and needs to be repeated from the beginning. As for the TOPSIS method, it’s a ranking decision against the best alternative because it calculates positive and negative ideal solutions. This support system using web base, where the data entered will be stored in MySQL database. The test results of Decision Support System for Providing Post-Pandemic Learning Infrastructure for Schools in the Madiun Regency Education Office Using Web-Based Analytical Hierarchy Process and Technique For Order Preference By Similarity To Ideal Solution Methods get results that are as expected with Black Box testing.